Calculating the bookmaker's margin: Why bets lose more on average than you are warned - Tadgh Hegarty; Karl Whelan (University College Dublin, UCD School of Economics, 2023)
If betting markets are efficient, then the expected loss rate on all bets on a game can be calculated from the quoted odds. Guides to sports betting tell bettors how to do this calculation of the predicted average loss rate. We show that if bookmakers set higher profit margins for bets with lower probabilities of winning (as implied by the evidence on favorite-longshot bias) then average loss rates across all bets will be higher than predicted by this widely-recommended calculation. We provide evidence from betting on soccer and tennis to illustrate that average realized loss rates on bets are consistently higher than predicted by the conventional calculation.
Keywords: G14; L83; Z20; 330; Market Efficiency; Sports Betting; Favorite-Longshot Bias